In Defense of Secrets - Dufourmantelle, Anne (Fordham University Press, 2021)
Frontmatter -- Contents -- Preamble -- I. Memories of the Secret -- Origins -- In the Crypt -- Etymology -- When the Secret Appears -- Occult Force -- II. The Secret’s Passions -- Lifting the Veil -- The Unavowable -- A Treasure, a Poison -- Genesis -- Storia I -- III. Being or Having -- The Last Secret -- The Body au secret -- Eroticism -- Storia II -- Storia III -- IV. Transparency and Truth -- Violations -- Dissimulations -- Surveillances -- Adaptations -- Mirages -- Big Data, Hyperconnection, Speed: The Spiral -- Archives -- Secret Societies -- The Unifying Secret -- V. An Ethics of the Secret -- Panopticum: Bentham, Kant, Constant -- Inappropriable -- Creative Power -- The Secret of Dreams -- Sex and Prayer -- Secret Sideration -- Jealousies -- The Conspiracy Theory -- VI. Toward Mystery -- Secret Nature -- Veils -- Legacies -- Aside -- A Part of One’s Own -- Secret of the Prophetic Voice -- Sacrifice -- Mystery’s Share -- Notes -- Bibliography